Tuesday
March 28, 2017

Post a New Question

Posted by on .

Q: Convert 4x^2 + 4y^2 -8x -16y -29 = 0 into standard form.

I first started by pairing the like terms together, getting:
4x^2 -8x + 4y^2 -16y = 29

The next step, I'm a little confused. I know I need to complete the square, but I'm not sure how to fully factor out the above equation before doing so. Can someone help me getting the factored form of the above equation?

Thanks!

  • math - ,

    4x^2 -8x + 4y^2 -16y = 29
    4(x^2 - 2x + ...) + 4(y^2 - 4y + ... ) = 29
    4(x^2 - 2x + 1) + 4(y^2 - 4y + 4) = 29 + 4 + 16
    4(x-1)^2 + 4(y-2)^2 = 49
    divide by 4
    (x-1)^2 + (y-2)^2 = 49/4

    looks like a circle with centre at (1,2) and radius 7/2

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question